Relative Handgrip Strength Is Inversely Associated with Metabolic Profile and Metabolic Disease in the General Population in China - Li, Dongxue; Guo, Guanghong; Xia, Lili; Yang, Xinghua; Zhang, Biao; Liu, Feng; Ma, Jingang; Hu, Zhiping; Li, Yajun; Li, Wei; Jiang, Jiajia; Gaisano, Herbert; et al. (Frontiers in Physiology, 2018)
Background: Absolute handgrip strength has been correlated with metabolic profile and metabolic disease. Whether relative handgrip strength is also associated with metabolic disease has not been assessed. This study aimed at assessing the association of relative handgrip strength with metabolic profile and metabolic disease in the general population in China. Methods: Data were derived from an ongoing cross-sectional survey of the 2013 National Physical and Health in Shanxi Province, which involved 5520 participants. Multiple linear regression or multiple logistic regression analysis were used to assess the association of absolute/relative handgrip strength with the metabolic profile, preclinical and established stages of metabolic diseases. Results: This study revealed that relative handgrip strength, that is when normalized to BMI, was associated with: 1) in both genders for more favorable blood lipid levels of high-density lipoprotein cholesterol (males: b=0.19(0.15,0.23); females: b=0.22(0.17, 0.28)), low-density lipoprotein cholesterol (males: b=-0.14(-0.23,-0.05); females: b=-0.19(-0.31,-0.18)), triglycerides (males: b=-0.58(-0.74, -0.43); females: b=-0.55(-0.74,-0.36)) and total cholesterol (males: b=-0.20(-0.31, -0.10); females: b=-0.19(-0.32, -0.06)); and better serum glucose levels in males (b=-0.30(-0.46,-0.15)). 2) lower risk of impaired fasting glucose in males (third quartile (OR=0.66(0.45-0.95)) and fourth quartile (OR=0.46(0.30-0.71)) vs first quartile) and dyslipidemia in both genders (third quartile (males: OR=0.65(0.48-0.87); females: OR=0.68(0.53-0.86)) and fourth quartile (males: OR=0.47 (0.35-0.64); females: OR=0.47(0.36-0.61)) vs first quartile). 3) lower risk of hyperlipidemia in both genders (third quartile (males: OR=0.66(0.50-0.87); females: OR=0.57(0.43-0.75)) and fourth quartile (males: OR=0.35(0.26-0.47); females: OR=0.51(0.38-0.70)) vs first quartile). However, contrary to relative handgrip strength, higher absolute handgrip strength was associated with unfavorable metabolic profiles and higher risk of metabolic diseases. These paradoxical associations were retained even after adjusted for BMI by employed a multivariate analysis. Conclusion: We conclude that measurement of relative handgrip strength can be used as a reasonable clinical predictor of metabolic health and disease.